A representação em Memórias póstumas de Brás Cubas e A consciência de Zeno - Ramos, Celeste [UNESP] (2001)
The aim of this study is to verify the motives which lead to a concordance in the reading and interpretation of Memórias póstumas de Brás Cubas (Epitaph of a Small Winner, a novel considered to be a milestone in the works written by Machado de Assis) and A consciência de Zeno (Confessions of Zeno, last novel by the Italian writer Ítalo Svevo), through the analysis of narrative resources and consonant enunciation procedures (perceptible through the narrator) used in the construction of narratives and contrastive discussion of converging themes, in order to detect the characteristics which make both novels to be innovative